COMPARATIVE EVALUATION OF EFFICACY AND SAFETY OF INTRAVENOUS FERRIC CARBOXYMALTOSE VERSUS IRON SUCROSE COMPLEX FOR THE TREATMENT OF MODERATE GRADE ANEMIA IN POST CAESAREAN SECTION WOMEN: A RANDOMIZED AND PROSPECTIVE STUDY - SAROJ, KOTHARI; SHIRALEE, RUNWAL (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Iron deficiency anemia is common in postpartum women in India. The present study is aimed at comparing the safety and efficacy of intravenous ferric carboxymaltose (FCM) with intravenous iron sucrose complex (ISC) in patients who underwent cesarean section and having moderate grade anemia in postpartum period. Methods: A prospective and comparative study was carried out in 100 post-cesarean section women with moderate grade anemia hemoglobin (Hb 7–9 g%) in Gajra Raja Medical College, Gwalior (M.P.) from February 2019 to August 2020. Subjects were randomly allocated to two groups, namely, FCM and ICS, 50 patients in each group. In group FCM, patients were infused with 1000 mg of FCM in a single dose on 4th post-operative day. Patients in ISC group were infused with ISC 200 mg in 100 mL normal saline on 3 alternate days on 4th, 6th, and 8th post-operative day. Mean, Hb mean corpuscular volume (MCV), mean corpuscular Hb (MCH), and MCH concentration (MCHC) were recorded before start of therapy and 15 days after treatment in all study subjects. Mean reticulocyte count was recorded before start of treatment and 2 days after completion of treatment that is on 6th and 10th post cesarean day in FCM and ICS group, respectively. Adverse drug reactions were recorded during the study period. Statistical analysis was done using Statistical Package for the Social Sciences software. Results: Mean Hb increased by 27% in FCM and by 19% in ISC group and is significant (*p<0.05) from baseline values. FCM showed significantly (**p<0.01) better response, than ISC group. Mean reticulocyte percent showed significant increase by 120% and 73% in FCM and ISC group, respectively, from the baseline and change in mean reticulocyte in FCM was significant (***p<0.001) as compared to ISC. The mean rise in MCV was 12% and 5% and MCH was by 10% and 1% in FCM and ISC group, respectively. FCM groups showed significantly better response (p<0.05) than ISC. However, in MCHC, there were 7% and 4% increase in FCM and ISC group, respectively, and on inter group comparison was not significant (p>0.05). Adverse effects noted during the study were mild and responded to symptomatic treatment. Sixteen percentage of FCM cases and 26% of ISC cases underwent adverse drug reactions that included nausea, vomiting, giddiness, and injection site reactions. Conclusion: FCM is more efficacious and safer than ISC, making it the first line of management in postpartum iron deficiency anemia.